(untitled) (SCIÉNDO INGENIUM, 2021)
This research was focused on demonstrating that the application of the "Speaking is wonderful" Program, based on playful strategies, stimulates the development of oral expression in first grade high school students from the "Antonio Torres Araujo" school in Trujillo. The research is quantitative, with a two-group quasi-experimental design. The population consisted of 173 students and the sample was 74 students: 37 (experimental group) and 37 (control group). The instruments applied were: the rubric, the pretest and the posttest, which were validated by expert judgment, obtaining a validity: 0.92 (V-Aiken) and reliability: 0.78 (KR20). The pretest and postest tests consisted of four levels: Starting, Process, Expected and Outstanding; In the pretest, 54% of students showed a low level in oral expression. However, after applying the postest, 62% improved their average to 16.6 points, reaching the “expected” level; At the level of dimensions, improvements were observed in “pronunciation” (57%); "Coherence" (56%); "Fluency" (64%); "Interaction" (65%) reaching the "expected" level. In conclusion, the program had a significant influence (sig = 0.000 <0.05%) in the development of oral expression in the first-grade students of the “Antonio Torres Araujo” school.